Formation of carbon Cottrell atmospheres and their effect on the stress field around an edge dislocation. (1st March 2017) - Waseda, Osamu; Veiga, Roberto GA; Morthomas, Julien; Chantrenne, Patrice; Becquart, Charlotte S.; Ribeiro, Fabienne; Jelea, Andrei; Goldenstein, Helio; Perez, Michel
Abstract: Biased Metropolis Monte-Carlo is employed to build a carbon Cottrell atmosphere around an edge dislocation. A novel method involving only local minimisation during the Metropolis scheme allows to deal with a million-atom system within a reasonable computation time. In this study, it is discovered that (i) the carbon atoms occupy interstitial sites not only in the traction zone, but also in the compression zone; (ii) local carbon concentrations of approximately 10at% are in good agreement with experimental values; (iii) the saturation of the Cottrell atmosphere does not originate from the stress-field around the atmosphere but from repulsive carbon-carbon interactions only. Graphical Abstract: